Subcutaneous device-free islet transplantation - Zhou, Xudong; Xu, Zhiran; You, Yanqiu; Yang, Wangrong; Feng, BingZheng; Yang, Yuwei; Li, Fujun; Chen, Jibing; Gao, Hongjun (Frontiers in Immunology, 2023)
Diabetes mellitus is a chronic metabolic disease, characterized by high blood sugar levels; it affects more than 500 million individuals worldwide. Type 1 diabetes mellitus (T1DM) is results from insufficient insulin secretion by islets; its treatment requires lifelong use of insulin injections, which leads to a large economic burden on patients. Islet transplantation may be a promising effective treatment for T1DM. Clinically, this process currently involves directly infusing islet cells into the hepatic portal vein; however, transplantation at this site often elicits immediate blood-mediated inflammatory and acute immune responses. Subcutaneous islet transplantation is an attractive alternative to islet transplantation because it is simpler, demonstrates lower surgical complication risks, and enables graft monitoring and removal. In this article, we review the current methods of subcutaneous device-free islet transplantation. Recent subcutaneous islet transplantation techniques with high success rate have involved the use of bioengineering technology and biomaterial cotransplantation—including cell and cell growth factor co-transplantation and hydrogel– or simulated extracellular matrix–wrapped subcutaneous co-transplantation. In general, current subcutaneous device-free islet transplantation modalities can simplify the surgical process and improve the posttransplantation graft survival rate, thus aiding effective T1DM management.